Occurrence of valvar heart disease in acute rheumatic fever without evident carditis: colour-flow Doppler identification. Issue 6 (June 1992) - Folger, G M; Hajar, R; Robida, A; Hajar, H A
Abstract : OBJECTIVE--To determine the frequency of occurrence of mitral and aortic valvar regurgitation in rheumatic children in whom there was no evidence of carditis acutely or at an earlier attack. DESIGN--Colour flow Doppler imaging was used in a non-randomised study of sequentially admitted children who met the criteria for acute rheumatic fever without clinically evident carditis and patients in whom the disease was quiescent after a previous attack of rheumatic fever. Two separate control groups were used for comparison of the echocardiographic findings, and a group of patients with confirmed rheumatic carditis was included for comparison of acute phase and antistreptococcal reactants. SETTING--A general hospital with the only paediatric inpatient department in Qatar. PATIENTS--From November 1988 to October 1990, 11 children were studied during the acute rheumatic period. In seven additional children the disease was quiescent when they were studied 18 to 36 months after a documented episode of acute rheumatic fever in which there was no evidence of carditis. The control patients were all studied during the same period. MAIN OUTCOME MEASURE--Detection of mitral and aortic regurgitation in patients without clinical evidence of rheumatic carditis in the acute or quiescent stages of the disease. RESULTS--Mitral or mitral and aortic regurgitation was found in 10 of the 11 children studied in the acute rheumatic period. None had a murmur or other evidence of carditis. In all the cases studied the valvar insufficiency was mild. Four of the children studied late in the quiescent period had either aortic or mitral insufficiency by colour flow Doppler evaluation; two children who had previously had valvar insufficiency no longer showed this, and one child without positive findings in the acute phase remained without insufficiency. None of the non-rheumatic control subjects showed mitral or aortic regurgitation. CONCLUSIONS--Colour flow Doppler imaging is a useful method of identifying subclinical mitral and aortic valvar disease at all stages of rheumatic fever when carditis cannot be otherwise detected and is a valuable addition to current diagnostic criteria.